Mixed-Orientation Marriages: An Analysis on Heterosexual Wife Legal Redress in Malaysia - Din, Hanis Nabihah Binti Hizamul-; Rahim, Rohani Abdul; Fandi, Fieza Fazlin Binti; Yaccob, Mohd Fadhly Bin; Yahanan, Annalisa (International Journal of Asian Social Science, 2018)
Mixed orientation marriages refers to marriages involving a partner who is gay or lesbian while the other partner may be heterosexuals or bi-sexual as well. Parties to such marriage are men and women who are gender fluid or transgender who wish to maintain their relationship that exist before or after the existing marriage commenced. In United States of America, there are as many as three million of such marriages – perhaps even more. Homosexuality or bisexuality is illegal in Malaysia and thus, the existence of mixed orientation marriage in Malaysia often hide behind a normal marriage. It has been difficult to quantify such marriage unless the courts that handle divorce matters identified such grounds to these divorces. Plus, mixed orientation marriage is an oppression towards the wives who are heterosexual. This paper will dwell on; (a) the definition of mixed-orientation marriage; (b) the factors that cause a bisexual husband to pursue a marriage with a heterosexual wife without her knowing of the fact ; (c) to find out the effects of such relationships to a heterosexual spouse in terms of her health, emotion and psychological impacts; (d) To identify the legal redress on heterosexual wife and her rights in such marriage; and (e) to analyse some strategies and the legal remedies available to deal with such kind of marriages, which denied the vary basis of contractual relationship acknowledge by civil and sharia marriages laws in Malaysia.